Registration and signal processing in measuring system for monitoring leaks of NPP pipeline fittings - E. A. Abidova; V. I. Ratushny (Омский научный вестник)
The article is devoted to the problem of identification of leakiness of pipeline fittings. A measuring system for leak monitoring is described. In contrast to the organoleptic approach adopted in practice, automatic signal processing is proposed, followed by a conclusion about the tightness of the valve. The automatic processing is based on an algorithm based on the analysis of the singular spectrum, which provides an increase in sensitivity. The effectiveness of the complex is confirmed by the test results of the measuring complex using a hydraulic stand.